Effects of ceftiofur and chlortetracycline treatment strategies on antimicrobial susceptibility and on tet(A), tet(B), and bla[subscript CMY-2] resistance genes among E. coli isolated from the feces of feedlot cattle - Kanwar, Neena; Scott, Harvey Morgan; Norby, Bo; Loneragan, Guy H.; Vinasco-Torres, Javier; McGowan, Matthew; Cottell, Jennifer L.; Chengappa, M. M.; Bai, Jianfa; Boerlin, Patrick (My University, 2013)
A randomized controlled field trial was conducted to evaluate the effects of two sets of treatment strategies on ceftiofur and tetracycline resistance in feedlot cattle. The strategies consisted of ceftiofur crystalline-free acid (CCFA) administered to either one or all of the steers within a pen, followed by feeding or not feeding a therapeutic dose of chlortetracycline (CTC). Eighty-eight steers were randomly allocated to eight pens of 11 steers each. Both treatment regimens were randomly assigned to the pens in a two-way full factorial design. Non-type-specific (NTS) E. coli (n = 1,050) were isolated from fecal samples gathered on Days 0, 4, 12, and 26. Antimicrobial susceptibility profiles were determined using a microbroth dilution technique. PCR was used to detect tet(A), tet(B), and bla[subscript CMY-2] genes within each isolate. Chlortetracycline administration greatly exacerbated the already increased levels of both phenotypic and genotypic ceftiofur resistance conferred by prior CCFA treatment (P<0.05). The four treatment regimens also influenced the phenotypic multidrug resistance count of NTS E. coli populations. Chlortetracycline treatment alone was associated with an increased probability of selecting isolates that harbored tet(B) versus tet(A) (P<0.05); meanwhile, there was an inverse association between finding tet(A) versus tet(B) genes for any given regimen (P<0.05). The presence of a tet(A) gene was associated with an isolate exhibiting reduced phenotypic susceptibility to a higher median number of antimicrobials (n = 289, median = 6; 95% CI = 4–8) compared with the tet(B) gene (n = 208, median = 3; 95% CI = 3–4). Results indicate that CTC can exacerbate ceftiofur resistance following CCFA therapy and therefore should be avoided, especially when considering their use in sequence. Further studies are required to establish the animal-level effects of co-housing antimicrobial-treated and non-treated animals together.
Keywords: Ceftiofur; tet(A); tet(B); blaCMY-2; E. coli; Feedlot cattle; Chlortetracycline treatment